Aplicação subsidiária da Lei das Sociedades Anônimas às sociedades limitadas, análise da jurisprudência e a importância da customização do contrato social - Maier, João Rodrigo (2018)
With the purpose of ascertaining the application of an alternative law, when it is optional and when it is mandatory, notably to understand the implications of the subjection of a limited liability company to the rules of joint-stock companies, as a result of a choice by the quotaholders, this paper analyzes some of the possibilities of alternative application of the Corporations Law to a limited liability company, due to the option given in the sole paragraph of article 1,053 of the Civil Code. It also seeks to verify, by means of an analysis of the doctrine and the case law of the superior courts and some state courts, under which circumstances the Corporations Law was applied during the term of effectiveness of Decree No. 3,708/19, which set forth, in an imperative manner, the application of the law of joint-stock companies. Therefore, the purpose of this paper is to show the importance of including in the ex ante articles of association specific situations established in the Corporations Law – convenient to the quotaholders and to the company – and not covered by the Civil Code, even if there is a generic provision for the alternative application of the joint-stock companies law, so as to allow the quotaholders to have previously defined mechanisms to carry out the company’s businesses and mitigate, in such points, the possibility of court intervention.